GETTING TO KNOW FUTURE SPECIALISTS WITH INNOVATION: THE CASE OF ŠIAULIAI STATE COLLEGE - Balvočiūtė, Rasa; Ožalienė, Orinta (PROFESSIONAL STUDIES: Theory And Practice, 2023)
The article presents a study of future professionals’ knowledge of innovation. Šiauliai State College I-IV-year students formed the research sample group. 103 respondents took part in the survey. Students usually get acquainted with innovations from the press, via the Internet, Youtube channel or social networks, as well as during college lectures. Research has shown that students are best acquainted with technological innovation and the stage of generating innovation ideas. The higher education institution should strengthen the studies of other stages of innovation development, especially commercialization.